Effects of stearic acid on tensile, morphological and thermal analysis of polypropylene (PP)/dolomite (DOL) composites - Adik, Nik Nur Azza Nik (Animo Repository, 2016)
The effects of stearic acid treated dolomite (Sa-Dol) on the mechanical, morphological and thermal properties of polypropylene (PP) composite were studied. Prior treatment, raw dolomite was ground in planetar y mill using different grinding time to obtain the submicron size (under 10μm). Particle size and specific surface area of dolomite was analyzed and validated using particle size analyzer (Malvern Mastersizer) and Brunauer-Emmett-Teller (BET) method respectively. Dolomite with five filler loadings (5, 10, 15, 20 & 25%) were mixed with PP thermoplastic and were compounded using hot melt blending method. Fourier Transform Infrared (FTIR) spectroscopy confirms the successful of filler treatment using stearic acid according to the new peak at 2917 cm-1 attributed to the alkyl group that represented the addition of C-H bond. Tensile properties indicated that tensile strength of PP/Dol decreased with the increasing of filler loading for both systems. The elongation at break decreased with filler loading and showed better and improved result after treatment with stearic acid. The incorporation of stearic acid coated filler into PP matrix enhanced the break elongation of the composites that makes the composites more ductile. Morphological analysis using Scanning Electron Microscopy (SEM) proved better interfacial adhesion and less agglomeration of dolomite filler after treatment with stearic acid at low filler loading (5 wt.%).